The Concept of Protection for Children Victims of Bullying Based on the Indonesian Criminal Justice System and the Rules of International Law - Amadela Andra Dynalaida; Dina Desvita Pramesti Putri; Aulia Maharani; Niken Aulia Rachmat (The Indonesian Journal of International Clinical Legal Education, 2022)
Various national and international legal instruments have emphasized how the state should make efforts to protect children, including in cases of bullying. However, the existing regulations do not clearly define how the victims and perpetrators should be treated. This study aims to analyze and compare the concept of legal protection in cases of bullying in national and international laws. The method used in this research is a normative legal study. This method is used to analyze and compare several concepts of legal protection in cases of bullying in both national and international regulations. This study uses a comparative law study approach and a statute approach. The location of this research is not carried out through field research but through literature review and document study. Supporting data in this study were also obtained from various data on the internet and printed sources. The results of the study indicate that the state is obliged to fulfill, protect, and respect the rights of the child, is obliged and responsible in formulating and implementing policies in the field of implementing child protection, having the obligation and responsibility to provide support for facilities, infrastructure, and the availability of human resources in the implementation of child protection. guarantee the protection, maintenance, and welfare of the child by taking into account the rights and obligations of parents, guardians, or other persons who are legally responsible for the child, as well as supervising the implementation of child protection.